Seasonal anomaly in variations of global distributions of F2-layer electron density according to CCIR model - Grinchenko, S. V. (НТУ "ХПІ", 2014)
There are presented the global distributions of electron density ne maxF2 and height hmaxF2 of the main maximum of ionosphere. There are analyzed the basic regularities of longitude-latitudinal variations of these parameters in the northern and southern hemispheres. The main attention is given to the effect of seasonal anomaly. It is shown that, according to calculations by the CCIR model seasonal anomaly appears at latitudes between 15 and 60 degrees N. approximately from 9 to 12 hours of local time. In the southern hemisphere the seasonal anomaly is not observed.

Побудовано планетарні розподіли електронної концентрації ne maxF2 і висоти hmaxF2 головного максимуму іоносфери. Проаналізовано основні закономірності довготно-широтних варіацій цих параметрів в північній і південній півкулях. Основна увага приділена ефекту сезонної аномалії. Показано, що згідно з розрахунками за моделлю CCIR сезонна аномалія проявляється на широтах від 15° до 60° пн. ш. приблизно з 9 до 12 години місцевого часу. У південній півкулі сезонна аномалія не спостерігається.
Keywords: CCIR model; IRI; NeQuick model; global distribution of ionospheric parameters; geographical anomaly; seasonal anomaly; December anomaly; semiannual anomaly; Visual Fortran; модель CCIR; модель NeQuick; планетарний розподіл іоносферних параметрів; географічна аномалія; сезонна аномалія; груднева аномалія; піврічна аномалія